2015
DOI: 10.15287/afr.2015.473
|View full text |Cite
|
Sign up to set email alerts
|

Time expenditure in computer aided time studies implemented for highly mechanized forest equipment

Abstract: Abstract. Time studies represent important tools that are used in forest operations research to produce empirical models or to comparatively assess the performance of two or more operational alternatives with the general aim to predict the performance of operational behavior, choose the most adequate equipment or eliminate the useless time. There is a long tradition in collecting the needed data in a traditional fashion, but this approach has its limitations, and it is likely that in the future the use of prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…DES model construction also requires a considerable amount of data, such as time elements of individual machines and their probability distributions, and it is often the case that sufficient data are not available in forest operations to make DES modeling feasible. Although modern data acquisition technologies (e.g., auto-video recording, GPS tracking, sensors) can help access operational data more easily and frequently [47][48][49], long-term field data collection is still necessary to obtain a representative sample of field operations and thus ensure quality output. Also, the large amount of random inputs in DES modeling can make it difficult to interpret the output in simple terms, especially for highly complex systems [50].…”
Section: Des Model Drawbacksmentioning
confidence: 99%
“…DES model construction also requires a considerable amount of data, such as time elements of individual machines and their probability distributions, and it is often the case that sufficient data are not available in forest operations to make DES modeling feasible. Although modern data acquisition technologies (e.g., auto-video recording, GPS tracking, sensors) can help access operational data more easily and frequently [47][48][49], long-term field data collection is still necessary to obtain a representative sample of field operations and thus ensure quality output. Also, the large amount of random inputs in DES modeling can make it difficult to interpret the output in simple terms, especially for highly complex systems [50].…”
Section: Des Model Drawbacksmentioning
confidence: 99%
“…Considering similar examples from 20 years ago, the efficiency of feller-bunchers in timber production has increased with the developments in forest machine technology. Furthermore, the time study analysis with the help of software can easily find the best regressors for highly mechanized forest equipment (Mușat et al 2015). It can be suggested that mechanized harvesting with a feller-buncher can be very productive; however further studies on harvesting productivity of feller-bunchers are required for optimum selection of the carrier platform and equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Borz et al 2014) and it is particularly useful when the researcher presence in the field is either not possible or not advisable. For such an approach, however, the processing effort at the office has been proved to be resource intensive in some cases, depending on the complexity of the studied system, and therefore on the number of work elements within a work cycle (Musat et al 2016).…”
Section: Time Consumptionmentioning
confidence: 99%